2009
DOI: 10.1080/08860220802669826
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin System Polymorphisms: A Risk Factor for Progression to End-Stage Renal Disease in Vesicoureteral Reflux Patients

Abstract: Aim. Renin-angiotensin system (RAS) gene mutations have been implicated as a risk factor for the presence and progression of renal disease in vesicoureteral reflux (VUR). However, the results are contradictory, and the effects of RAS polymorphisms in VUR patients with end-stage renal disease (ESRD) have not been defined yet. This study was designed to evaluate the angiotensin-converting enzyme insertion/deletion (ACE-I/D), angiotensinogen (AGT) M235T, and angiotensin II receptor type 1 (ATR1) A1166C and type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…also performed a study in a Chinese population and reported that the DD genotype might predispose the individual to increased risk of progression to ESRD in IgA nephropathy patients. Akman et al 48 . performed an investigation on Turkish population and reported that the DD genotype was a genetic susceptibility factor for progression to ESRD in vesicoureteral reflux patients.…”
Section: Discussionmentioning
confidence: 99%
“…also performed a study in a Chinese population and reported that the DD genotype might predispose the individual to increased risk of progression to ESRD in IgA nephropathy patients. Akman et al 48 . performed an investigation on Turkish population and reported that the DD genotype was a genetic susceptibility factor for progression to ESRD in vesicoureteral reflux patients.…”
Section: Discussionmentioning
confidence: 99%
“…The I/D polymorphism of the ACE gene and plasma concentration were studied as a cluster of cardiovascular risk factors that could contribute to excess metabolic cardiovascular and renal risks in MHD patients compared with patients undergoing CT. Several reports linked this polymorphism to the development and progression of chronic renal diseases of different etiologies [30-33]. …”
Section: Discussionmentioning
confidence: 99%
“…Children who have had an infection of kidney parenchyma have a risk of persistent kidney damage which may result in kidney scarring, hypertension, recurrent urinary tract infections, reflux nephropathy, complications in later pregnancies or, in the worst case, renal insufficiency (RUSHTON, 1997;AKMAN et al, 2009). The presence of vesicoureteral reflux (VUR) is considered as a risk factor for a parenchymal kidney infection and subsequent scarring (NAKAI et al, 2003;MOHANAN et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Due to dysfunction of the ventricular mechanism of the vesicoureteral compound, manifested by the return of urine from the urinary bladder to the ureter, VUR is the most common anomaly of the urinary tract in children. The ureterovesical junction normally functions as a one-way folding valve which slowly collapses during the filling phase, preventing the retractable return of urine into the ureter and kidney (AKMAN et al, 2009;PURI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%